Assessing the effect of Essigella californica on Pinus radiata at two sites in New Zealand - Watson, M.C.; Kriticos, D.J.; Drayton, G.M.; Teulon, D.A.J; Brockerhoff, E.G. (New Zealand Plant Protection, 2008)
The impact of the exotic aphid Essigella californica (Essig) on the health and growth of Pinus radiata DDon in New Zealand was examined by comparing trees treated with a systemic insecticide with untreated trees at two climatically contrasting sites over three seasons (20062008) Upper crown yellowing thought to be associated with E californica was not affected by insecticide treatment However on insecticidetreated trees aphid numbers were reduced and tree diameter increased in the final year at both sites Significantly more aphids were recorded at McLeans Island Forest than Kaingaroa Forest in all years The incidence of the needlecast fungus (Cyclaneusma minus) was also greater at McLeans Island in support of a possible relationship between E californica and C minus Compared with its effect in Australia E californica appears to have a low pest status in New Zealand